-6(n+3)+19=-2n-11

Simple and best practice solution for -6(n+3)+19=-2n-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(n+3)+19=-2n-11 equation:


Simplifying
-6(n + 3) + 19 = -2n + -11

Reorder the terms:
-6(3 + n) + 19 = -2n + -11
(3 * -6 + n * -6) + 19 = -2n + -11
(-18 + -6n) + 19 = -2n + -11

Reorder the terms:
-18 + 19 + -6n = -2n + -11

Combine like terms: -18 + 19 = 1
1 + -6n = -2n + -11

Reorder the terms:
1 + -6n = -11 + -2n

Solving
1 + -6n = -11 + -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
1 + -6n + 2n = -11 + -2n + 2n

Combine like terms: -6n + 2n = -4n
1 + -4n = -11 + -2n + 2n

Combine like terms: -2n + 2n = 0
1 + -4n = -11 + 0
1 + -4n = -11

Add '-1' to each side of the equation.
1 + -1 + -4n = -11 + -1

Combine like terms: 1 + -1 = 0
0 + -4n = -11 + -1
-4n = -11 + -1

Combine like terms: -11 + -1 = -12
-4n = -12

Divide each side by '-4'.
n = 3

Simplifying
n = 3

See similar equations:

| L=1/2pV^2SC | | 3.2+(h+5.1)= | | Y=(-1/5)-20-2 | | 45/B=15 | | -4-4s=-8-2s | | 63/60=x/180 | | 4a/3=160 | | y/6-3 | | 4x(4x-5b)+3= | | 3+3d= | | 9b^2-48b+48+15b^2-20b=20b-5b^2 | | 22v-9v-8v-v-3v-1=34 | | 100[0.03(p+9)]= | | -28=(4/5)d | | 3x-1+2x^2(6)= | | 7x-(3x-9)= | | 3y+17=-2y+24 | | -6d-10=-5d | | 6b-3b+4b-4b+1=25 | | x^2+y^2-2x+8y-23=0 | | -(5a+9)-5(a-8)= | | (2x+1)(2x-1)=y | | -2(z+3)-z+-z-4(z+2)= | | 2x+84=3.333333333 | | 0+.75x=7.5+.5x | | 2x+84=3 | | (2/3)t=9 | | 6b-3b+4b+1=25 | | -3g-3= | | -8+3u=-6+5u-8 | | -5.8(2p+4)-1.6(3p-5)= | | 2x+1+y=5y+7x+11 |

Equations solver categories